1994
DOI: 10.1128/iai.62.10.4145-4152.1994
|View full text |Cite
|
Sign up to set email alerts
|

Role of interleukin-8 (IL-8) and an inhibitory effect of erythromycin on IL-8 release in the airways of patients with chronic airway diseases

Abstract: To evaluate of the role of interleqkin-8 (IL-8), a chemotactic cytokine, in the continuous neutrophil accumulation in the airways of patients with chronic airway disease (CAD) and persistent Pseudomonas aeruginosa infection, we investigated the cell population, IL-8 levels, I-1B levels, tumor necrosis factor (TNF) activities, and neutrophil elastase (NE) activities of bronchoalveolar lavage (BAL) fluids in 17 CAD patients (with P. aeruginosa infections [CAD+PA], n = 9; without any bacterial infections [CAD-PA]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(80 citation statements)
references
References 50 publications
3
76
0
1
Order By: Relevance
“…36,72 The level of IL-8 in BAL fluid markedly decreases along with the neutrophil number and its elastase concentration. 73 EM dose-dependently inhibited IL-8, IL-6 and granulocyte-macrophage colony-stimulating factor secretion from epithelial cells in vitro using a human airway epithelial cell line. 74,75 Recently, it was revealed that EM suppressed the activation of nuclear factor-kappa B and activator protein-1 in human bronchial epithelial cells and subsequently inhibited IL-8 mRNA expression on epithelial cells.…”
Section: Inhibition Of Neutrophil Activitymentioning
confidence: 93%
“…36,72 The level of IL-8 in BAL fluid markedly decreases along with the neutrophil number and its elastase concentration. 73 EM dose-dependently inhibited IL-8, IL-6 and granulocyte-macrophage colony-stimulating factor secretion from epithelial cells in vitro using a human airway epithelial cell line. 74,75 Recently, it was revealed that EM suppressed the activation of nuclear factor-kappa B and activator protein-1 in human bronchial epithelial cells and subsequently inhibited IL-8 mRNA expression on epithelial cells.…”
Section: Inhibition Of Neutrophil Activitymentioning
confidence: 93%
“…Earlier studies found that macrolide antibiotics influence the endotoxin-induced production of cytokines by the host, as well as production induced by Gram positive bacteria [13][14][15][16][17]. However, the clinical relevance of this finding is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…We tried long-term low-dose erythromycin therapy in the present patient because of its anti-inflammatory effects. 13,14 Low-dose erythromycin therapy led to disappearance of recurrent pneumonia. However, we could not sufficiently explain the mechanism of efficacy of low-dose erythromycin therapy in recurrent pneumonia.…”
Section: Discussionmentioning
confidence: 99%